2022
DOI: 10.1111/jre.12980
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid/caprolactone) bilayer membrane blocks bacterial penetration

Abstract: Background and Objective:The clinical outcomes of guided tissue regeneration (GTR) or guided bone regeneration (GBR) procedures can be impaired if a bacterial infection develops at the surgical site. Membrane exposure is one of the causes of the onset of bacterial infection. Previously, we have fabricated a poly(lactic acid/caprolactone) (PLCL) bilayer membrane composed of a porous layer and a compact layer.The compact layer acts as a barrier against connective tissue and epithelial cells, and we hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
(102 reference statements)
1
14
0
Order By: Relevance
“…Col membrane presents a mesh-like structure, hydrophilic and permeable in aqueous environments, allowing greater cell infiltration. 14,15 PLGA shows interconnected pores that also allow cell infiltration, however the hydrophobic nature of this material may slow down permeability. PLCL is characterized by wide pores that permitted cells to infiltrate the porous layer, 14 though the presence of a compact layer in direct contact with the surgical flap prevented epithelial cell invasion of the bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…Col membrane presents a mesh-like structure, hydrophilic and permeable in aqueous environments, allowing greater cell infiltration. 14,15 PLGA shows interconnected pores that also allow cell infiltration, however the hydrophobic nature of this material may slow down permeability. PLCL is characterized by wide pores that permitted cells to infiltrate the porous layer, 14 though the presence of a compact layer in direct contact with the surgical flap prevented epithelial cell invasion of the bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be attributed to the synergistic effect of chemical composition and fibers alignment on cell proliferation and adhesion. 208 Abe et al 209 found that the PLCL bilayer membrane had reduced bacterial adhesion and blocked bacterial penetration, compared to the membranes of collagen and PLGA (Figure 13a), leading to a favorable outcome for regenerative treatments. Moreover, colony-forming units (CFU) counts of the incubated bacteria throughout the experimental period up to 72 h (Figure 13b), revealing that (1) P. gingivalis showed that the PLCL membrane had fewer adherent cells compared to the PLGA or Col membranes.…”
Section: Pegmentioning
confidence: 99%
“…Bacterial infection in GBR membranes is another major problem, leading to complications in the procedure. The membrane is used to cover the bone defect and protect it from bacterial contamination, but if it becomes infected, it can impede the healing process and lead to potential failure. , The most common bacterial species that cause infection in GBR membranes are Streptococcus spp, Staphylococcus spp, and Porphyromonas gingivalis . , One common solution reported is to directly dope the membrane with antibiotics to minimize the risk of infection. , However, the uncontrollable continuous release of antibiotics was reported as the main drawback, hindering their real-world application as anti-infectious membranes.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations